PENANAMAN DISIPLIN PADA ANAK USIA DINI - Ghofar, Abdul (AL-MISBAH (Jurnal Islamic Studies), 2013)
Early age is the golden age that only occurs once in the development of human life. This period is as well as a critical period in a child?s development. If at this time the child receives less attention,  it is feared that the child can not grow and develop optimally. One of the important things to get attention associated with education given at an early age is giving values of discipline through education in kindergarten. In developing the values   of discipline for early childhood needs to be done with extreme caution. This is because early childhood is children who are in the concrete operational stage of development as proposed by Piaget, while the value of discipline are common abstract concepts, so in this case the children can not necessarily accept what is taught by teachers / parents with abstract nature quickly. For that old man ?or? teacher ?must be very clever in choosing and determining the method to be used to instill the values of discipline to the child so that the message can be really understood by students for the provision of life in the future There are somes methods to instill the discipline values to the  children that can be offered  in this paper, namely the model of  authoritarian, permissiveness and democracy discipline, or method  of storytelling  or it could be a habituation method. According to the writer, of course each of these methods has its advantages and disadvantages. Therefor teachers or parents in  instilling the discipline values   to the children shall be adjusted situation and condition of the child and understand the theories of child development offered by the experts